EVALUASI LOGGING TRUK BERDASUKAN UMUR PAKAI, PRODUKTMTAS DAN BIAYAANGKUTAN - Sukanda Sukanda (Jurnal Penelitian Hasil Hutan, 1991)
In mMy forest coneuions  today, old loggin1 truelu of j   - 9 yean old ore. being med.  Thae  truda  will be continuo,ly uud  "'  long,a  ,,,,,,p,a.ra  ore available Md the equipment can be repaired. TM result, ore low productivit) ..ind laigla co,t.An obsnvotion in the field on 9 and 2-yeor old logging trucks in <AntralKalimantan ,ltow,  Ilse folli>winf   ruultJ  :1.For logging truclc condition o/9-year old, effecti11e working lime if 63 9' and productivity if  10,921m'lyeor wlsiela t1re loWff' .,,.,,,. tluJu.     for logging truck of 2-year old wills effective working hour of 80,5 9' and producti11ilyof 18,678 m.~lyeor.2.Rawling wills lo1ging truck of 9-yeor old if  more ·upensiH  than that of logging. truck of 2-yeor old, _Le  : Rp 4,940lm'l5o 1cm  (  Rp99lm3/lcm) Md  Rp 4,360/m3150 lcm ( Rp 87/m3/lcm), rup«tively  which mean, the dilferenee of $80/m3/$0 km  ( Rp 12/m3ilcm ).3. Due to large amount of maintenance cost, upeciaUy spare part cost than reached 54 9' of tM total cost, the 9-yeor old loainl   trucluore not ef/ieknt_ ~ymore and, dstre/ore, need to be replaced.